Effect of defect length upon burst capacity of composite repaired pipe - Lim, Kah Qi (2019)
Pipeline system is one of the infrastructures that are essential in petrochemical industries as it is uses to transport oil and gas. However, pipelines will start to damage and deteriorate after being used for some years, especially the happening of corrosion which will reduce the thickness of pipeline and the remaining strength of the pipe and consequently lead to failure once the remaining strength unable to withstand operating pressure of the pipeline. Hence, additional strength from repairing job needs to be provided, for instance, by using fibre-reinforced polymer (FRP) composites. Unlike the assessment codes, the repair code that use to determine the remaining strength of the corroded pipe does not include the defect geometries such as defect length. In this study, burst pressure of the composite repaired pipeline with different defect lengths and the effect of the defect length upon the burst capacity of composite repaired pipe is investigated. The study is carried out by a finite element analysis (FEA) on various defective pipe with different defect length size. The results show that the difference of the burst pressure subjected to various defect length is 15.59% and this had proved that there is an effect of defect length upon the burst capacity of composite repaired pipe. This finding can be very useful for optimizing the existing repair design.